2013
DOI: 10.4038/tare.v15i1.5236
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation Of Tree Species Populations Under Different Land Use Types Within The University Of Port Harcourt Environs

Abstract: Impact of land use changes and varying levels of habitat disturbance on tree populations was evaluated using the spatial analogue technique of studying ecosystem dynamics. Three sites with low, moderate, and high levels of disturbance were purposively chosen from the Biodiversity Conservation Area (BCA), an Unprotected Secondary Regrowth (USR), and an Arable Farmland (AF) respectively, for the study. Tree density and alpha diversity were evaluated in each site. The level of tree species compositional similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In coffee agroforests, the management is protection oriented with where as in adjoining forests through protection oriented which is subjected to disturbances due to grazing, illegal felling and collection of non-timber forest products. Chima and Uwaegbulem (2012) assessed tree species populations under different land use systems in Port Harcourt region of Nigeria and reported that tree species richness was higher in biodiversity conservation area than the unprotected secondary regrowth and arable farmland. Murthy et al, (2016) reported on Western Ghats of India where the more disturbed evergreen and moist deciduous forest had low species diversity compared to less disturbed forests.…”
Section: Species Diversity and Vegetation Structurementioning
confidence: 99%
“…In coffee agroforests, the management is protection oriented with where as in adjoining forests through protection oriented which is subjected to disturbances due to grazing, illegal felling and collection of non-timber forest products. Chima and Uwaegbulem (2012) assessed tree species populations under different land use systems in Port Harcourt region of Nigeria and reported that tree species richness was higher in biodiversity conservation area than the unprotected secondary regrowth and arable farmland. Murthy et al, (2016) reported on Western Ghats of India where the more disturbed evergreen and moist deciduous forest had low species diversity compared to less disturbed forests.…”
Section: Species Diversity and Vegetation Structurementioning
confidence: 99%